2012
DOI: 10.1021/ja308205d
|View full text |Cite
|
Sign up to set email alerts
|

Rollover Cyclometalation Pathway in Rhodium Catalysis: Dramatic NHC Effects in the C–H Bond Functionalization

Abstract: Organometallic chelates are readily obtained upon coordination of metal species to multidentate ligands. Because of the robust structural nature, chelation frequently serves as a driving force in the molecular assembly and chemical architecture, and they are used also as an efficient catalyst in numerous reactions. Described herein is the development of a Rh(NHC) catalytic system for the hydroarylation of alkenes and alkynes with 2,2'-bipyridines (bipy) and 2,2'-biquinolines; the most representative chelating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(68 citation statements)
references
References 108 publications
0
59
0
4
Order By: Relevance
“…Im Anschluss an diese Entdeckung wurde eine Auswahl an Katalysatoren fürd ie Alkylierung von 2-Pyridylarenen und ähnlichen Substraten mit Alkenen beschrieben. [161] Ackermann et al demonstrierten, dass Ruthenium(II)-Komplexe effizient die Alkylierung ähnlicher Substrate in Gegenwart eines sperrigen Carboxylats zur Unterstützung der Spaltung der C-H-Bindung katalysieren (Schema 37, Einschub * 3). Analog zu den katalytischen Systemen auf Rhodiumbasis folgte die Erweiterung auf die ortho-Alkylierung von 2-Pyridylarenen ebenso wie 1-Isochinolin-und 1-Pyrazolderivaten mit konjugierten Ketonen (Schema 37, Einschub * 2) [159] -e ine Reaktion, die auch ausgehend von den entsprechenden Allylalkoholen in Gegenwart eines zusätzlichen Oxidationsmittels durchgeführt werden kann [81b] -s owie auf atropselektive Alkylierungen [160] und auf die zweifache Alkylierung von 2,2'-Bipyridinen.…”
Section: Alkylierung Mit Alkenenunclassified
See 1 more Smart Citation
“…Im Anschluss an diese Entdeckung wurde eine Auswahl an Katalysatoren fürd ie Alkylierung von 2-Pyridylarenen und ähnlichen Substraten mit Alkenen beschrieben. [161] Ackermann et al demonstrierten, dass Ruthenium(II)-Komplexe effizient die Alkylierung ähnlicher Substrate in Gegenwart eines sperrigen Carboxylats zur Unterstützung der Spaltung der C-H-Bindung katalysieren (Schema 37, Einschub * 3). Analog zu den katalytischen Systemen auf Rhodiumbasis folgte die Erweiterung auf die ortho-Alkylierung von 2-Pyridylarenen ebenso wie 1-Isochinolin-und 1-Pyrazolderivaten mit konjugierten Ketonen (Schema 37, Einschub * 2) [159] -e ine Reaktion, die auch ausgehend von den entsprechenden Allylalkoholen in Gegenwart eines zusätzlichen Oxidationsmittels durchgeführt werden kann [81b] -s owie auf atropselektive Alkylierungen [160] und auf die zweifache Alkylierung von 2,2'-Bipyridinen.…”
Section: Alkylierung Mit Alkenenunclassified
“…Analog zu den katalytischen Systemen auf Rhodiumbasis folgte die Erweiterung auf die ortho-Alkylierung von 2-Pyridylarenen ebenso wie 1-Isochinolin-und 1-Pyrazolderivaten mit konjugierten Ketonen (Schema 37, Einschub * 2) [159] -e ine Reaktion, die auch ausgehend von den entsprechenden Allylalkoholen in Gegenwart eines zusätzlichen Oxidationsmittels durchgeführt werden kann [81b] -s owie auf atropselektive Alkylierungen [160] und auf die zweifache Alkylierung von 2,2'-Bipyridinen. [161] Ackermann et al demonstrierten, dass Ruthenium(II)-Komplexe effizient die Alkylierung ähnlicher Substrate in Gegenwart eines sperrigen Carboxylats zur Unterstützung der Spaltung der C-H-Bindung katalysieren (Schema 37, Einschub * 3). [162] Pyridine,Imidazole und Pyrazole fungierten als effiziente dirigierende Gruppen zur Herstellung der linearen ortho-alkylierten Produkte in hervorragenden Ausbeuten und Selektivitäten ohne konkurrierende Zweifachal-…”
Section: N-heteroarene Als Dirigierende Gruppenunclassified
“…Miura et al pioneeringly reported the catalytic reaction including the “rollover” cyclometalation pathway, where the Rh‐catalyzed consecutive C–H bond activation of 2,2′‐bipyridine in the reaction with silylacetylene gave the 3,3′‐dialkenylated product (Scheme a) . Chang et al focused on the use of “rollover” cyclometalation pathway using a Rh catalyst with an N ‐heterocyclic carbene ligand, which facilitates cleavage of a coordination bond due to its trans effect (Scheme b) . In these two examples, the “rollover” pathway was used for the C–H bond cleavage and the following intermolecular insertion of alkyne or alkene afforded the corresponding products .…”
Section: Introductionmentioning
confidence: 99%
“…Electron-deficient alkenes afford the desired products in excellent yields as single regioisomers. The reaction of 1c and styrene is also completely regioselective; however, the 6-phenylpyridine product 3cf undergoes a second C-H activation event, 12 resulting in a mixture of 3cf and 2-styrenyl- 3cf (eq 4). On the other hand, product alkenylation is not observed with oxime ester 1g .…”
mentioning
confidence: 99%